(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Additive manufacturing, famous as 3D printing, is a cutting-edge technology of the manufacturing process. Initially, the application of additive manufacturing was restricted to prototyping. Still, the advancement of technology and a wide choice of material for 3D printing made it affordable and applicable for many manufacturing industries. Presently, 3D printing is accurate, automated, affordable and thoroughly customizable for batch and continuous manufacturing of complex geometrical structures. The application of 3D printing in biomedical engineering is growing well. Multiple choices of 3D printing technology and a wide range of biomaterial provide a healthy platform for biomedical application. In this study, principles of additive manufacturing technologies, printing methods, and suitable material has been discussed to provide depth overview of the current scenario of 3D printing and provide a glimpse of the possible future of 3D printing.